Performance of Poplar Plantation under different levels of Nutrients in an Agroforestry System - Singh, Baljit; Gill, R.I.S.; Kaur, Navneet (Indian Forester, 2022)
Poplar (Populus deltoides Bartr.) has been adopted in agroforestry systems by farmers of north-western India owing to its fast growth. An experiment was conducted to standardize the nutrient requirement of poplar plantation during 6 years of growth for getting its better productivity. The treatments consisted of nine combinations (T2to T10) of N and P (as P2O5) in addition to an uncropped control (T1) of poplar plants. Every year, whole of P and 1/3rd N was applied during May after harvesting of wheat, 1/3rdN in July and the remaining 1/3rd N in September. The height and diameter at breast height (DBH) of plants were measured every year in the month of January and timber weight was calculated from these parameters. The DBH, height and timber weight of poplar plantation were lowest in uncropped control (19.01 cm, 17.56 m and 310 q/acre, respectively) and highest (21.46 cm, 20.10 m and 449 q/acre, respectively) with the application of N and P (as P2O5) @ N100P40, N150P80, N200P120, N250P160, N300P200 and N350P240g/plant (T6) during 1st, 2nd, 3rd, 4th, 5th and 6th year, respectively. However, the application of P during 4th, 5th and 6th year did not increase the timber weight over N application alone. The grain yield of wheat and fodder yield of pearlmillet decreased with increase in age of plantation. Net returns from the agroforestry system (crops and trees) were highest in T5 which were Rs. 408791 per acre Soil OC and available N and 6 . P were lowest in uncropped control (T1) and highest in T10 (tenth treatment) i.e., with the application of N and P @ N N150P80, N200P120, N250P160, N300P200,N350P240 and N400P280 g/plant during 1st, 2nd, 3rd, 4th, 5th and 6th year, respectively. Therefore, treatment T was better than other treatments for getting higher productivity 6 and better returns from poplar plantation.